A Hybrid STATCOM Approach to Enhance the Grid Power Quality associated with a Wind Farm - Adware, Ramchandra; Chandrakar, Vinod (Engineering, Technology & Applied Science Research, 2023)
The growing use of renewable energy sources in the production of electric power has certain adverse effects on power quality. A compensation system includes some additional devices, such as capacitors, compensators, or reactive power injection devices. FACTS devices, such as the Static Var Compensator (SVC), Dynamic Voltage Restorer (DVR), and Unified Power Quality Conditioner (UPQC), have become popular as power electronics become more sophisticated. This study investigated the properties of three significant compensating devices: SVC, STATCOM with PI controller, and hybrid STATCOM with a harmonic filter. Common power quality concerns, such as voltage sags and swells and the percentage of Total Harmonic Distortion (TDH), were taken into account during the initial modeling and performance analysis of the proposed system. The overall results showed that the proposed hybrid STATCOM system enhanced the power quality in wind energy systems more than the other two systems.